SvBLOCK: mitigating black hole attack in low-power and lossy networks. (4th February 2020) - Luangoudom, Sonxay; Tran, Duc; Nguyen, Tuyen; Tran, Hai Anh; Nguyen, Giang; Ha, Quoc Trung
The black hole is one of the well-known attacks that occur in Low power and Lossy Networks (LLNs). This paper presents a novel svBLOCK scheme to handle the black hole problem. svBLOCK is based on SVELTE, a real-time intrusion detection system (IDS) for the Internet of Things to reconstruct the destination oriented directed acyclic graph (DODAG) and validate the node availability. It is also equipped with mechanisms to provide authenticity over its control messages and isolate black holes from the LLNs. svBLOCK is implemented in Contiki OS and is evaluated under various attack scenarios. It demonstrates to achieve 98.5% true positive rate (TPR) at a false negative rate of 3.7%, while improving the packet delivery rate (PDR) by up to 47% with respect to the original SVELTE.